Christine Benoit, D77, and Bruce Gouin, D78, and their son Brendan Gouin, D09, at their house in Charlestown, Rhode Island for the Tufts Dental Magazine. Photo 061 - Ko, Melody (Tufts Archival Research Center, 2008)
Christine Benoit, D77, and Bruce Gouin, D78, and their son Brendan Gouin, D09, at their house in Charlestown, Rhode Island for the Tufts Dental Magazine. Benoit and Gouin are married and have been practicing together for years. They kept practicing while raising their two children.